The expression of aminoacyl-tRNA-synthetase-interacting multifunctional protein-1 (Aimp1) is regulated by estrogen in the mouse uterus. (5th January 2015) - Jeong, Ji-Hye; Park, Miree; Park, Miseon; Lim, Eun Jin; Kim, Hye-Ryun; Song, Haengseok; Park, Sang Gyu; Choi, Eun-Jin; Hong, Kwon-Ho; Lee, Dong Ryul; Ko, Jeong-Jae; Choi, Youngsok
Highlights: We examine the expression of Aimp1 in the mouse uterus. Aimp1 is exclusively localized in the luminal and glandular epithelium of the uterus. Estrogen treatment increased the expression of Aimp1 in ovariectomized mice. The promoter of Aimp1 contains a putative estrogen receptor binding element. We report the expression of Aimp1 is regulated during the estrous cycle and estrogen. Abstract: Aimp1 is known as a multifunctional cytokine in various cellular events. Recent study showed Aimp1 is localized in glandular epithelial, endothelial, and stromal cells in functionalis and basalis layers of the endometrium. However, the regulatory mechanism of Aimp1 in the uterus remains unknown. In the present study, we found that Aimp1 is expressed in the mouse uterus. Aimp1 transcripts were decreased at diestrus stage. However, the level of Aimp1 protein was significantly increased in the luminal epithelium in the uterine endometrium at estrus stage during the estrous cycle. We found that treatment of estrogen increased the expression of Aimp1 in the uterus in ovarectomized mice. We identified one estrogen receptor binding element (ERE) on mouse Aimp1 promoter. The activity of Aimp1 promoter was increased with estrogen treatment. Our findings indicate that Aimp1 might act as an important regulator to remodel the uterine endometrium and its expression might be regulated by estrogen during the estrous cycle. This will give us better understanding of the dynamic change of uterine remodeling during the estrous cycle.